IMPLEMENTATION OF GO RIDE PASSENGER INSURANCE IN ONLINE TRANSPORTATION DUE TO ACCIDENTS - Saputra, Arikha; Listyorini, Dyah (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The presence of online transportation is considered to really help the community in the process of mobilizing goods or people. Online transportation is currently very popular among the public, because online transportation is considered cheap and practical. Transportation is a system consisting of facilities and infrastructure, supported by management and human resources which form a service network that functions as a driver, driver and supporter of development. Protection by providing compensation for losses is an important basic basis in insurance, requiring the company to have a legitimate financial interest in the object or event being insured. In the context of online transportation, it is important for companies like Gojek to apply this principle in passenger accident life insurance. This research is a legal research using a normative juridical approach. The specifications of this research are analytical descriptive, because this research can provide a comprehensive, systematic picture and analysis of the realities in the field, especially regarding liability and insurance protection contained in legislation. Data collection is carried out by making observations and using applicable legislation. In carrying out transportation activities other than carrying out passenger trips, the transportation service provider is obliged to insure its liability, meaning that the public transportation company is obliged to compensate for losses suffered by passengers or goods senders due to negligence in carrying out transportation services. Based on article 237 paragraph (1) of the Road Traffic and Transportation Law, it is stated that public transportation companies are obliged to participate in an accident insurance program as a manifestation of their responsibility for insurance coverage for victims and public transportation companies are obliged to insure people employed as vehicle crew. The form of insurance protection provided by Gojek to passengers who use its services is the application of Article 302 of the Criminal Code. The online transportation service provider company Gojek provides insurance to passengers to ensure that travel is protected because passenger safety is Gojek's priority. The form of insurance protection for passengers in Gojek online transportation is stated in the GoRide Pasangger Insurance provisions.